Quantifying the Short-Run Macroeconomic Impacts of the COVID-19 Pandemic: A Macroeconometric Approach - John Paul P. Corpus; Margarita Debuque-Gonzales (Philippine Institute for Development Studies (PIDS), 2023)
While the COVID-19 pandemic's effects on the Philippine economy have been widely chronicled, there has not been an effort at an ex-post quantification of the pandemic's impacts using counterfactual analysis. This paper aims to fill this gap. Using a modified version of the PIDS small macroeconometric model, forecasts for 2020 and 2021 are generated to serve as counterfactual paths of key economic indicators in the pandemic's absence. The gap between the actual and counterfactual trajectories is interpreted as comprising the pandemic's impact. The impact estimates lend further evidence to the pandemic's severe and lasting effects on the real economy, with real output, private domestic spending (particularly investment), and the employment rate suffering significant negative deviations from their counterfactual levels. Model simulations also clarify the extent of the deterioration of public finances triggered by the pandemic, particularly on tax revenues, the fiscal balance, and government debt. On the other hand, the pandemic's estimated impacts on inflation and key domestic interest rates are less evident.
Keywords: 330; macroeconometric model; COVID-19 pandemic; Philippine economy